A proposed career counseling program and a model career monograph for Ateneo de Davao - Ipong, Della S. (Animo Repository, 1974)
This study aims to formulate a studied plan by which the career needs and vocational difficulties of Ateneo de Davao students can be responded to adequately so that their college preparation would find relevance to their future life. This study is composed of two parts : a proposed counseling program and a completed industrial monograph for career counseling. The proposal was a descriptive study based on three major sources : a survey of student needs of the Ateneo de Davao, a series of interviews with the Director of the Guidance Services, and extensive library research. Two hundred students for the second semester of 1973-74 composed the sample population for the survey of student needs. The counselors of the school were likewise asked for opinions and questions on student needs and career counseling activities of the school. Of the four counselors in the present program, three responded to the survey. Two sets of survey questionnaires were developed by the researcher, one for the students and another for the counselors. The second part of the study presented an example of a career information literature which was the result of personal interviews and written communications with the personnel managers of several banana companies in Davao City. Results of the survey disclosed that Ateneo de Davao college students were indeed bothered by problems classifiable as vocational. The three leading problem areas were : conflict between realistic and idealistic goals, fears of unemployment after graduation or dropping out of college, and inadequate information about courses of concentration and job opportunities. It was also found that a guidance program was in operation offering the following services : counseling, testing, information, individual inventory, referral, and research. Placement was likewise provided but under the Office of the Student Personnel Services. The survey revealed the poor influence the counselor has in the student's career planning. In the study, six services were proposed for the career counseling program. The basic services proposed were counseling, testing and information, and the proposed supportive services were placement, record system, and research. The program also proposed a mobilization of the information service through the help of teachers, department chairmen, the library staff, and the Director of Student Personnel Services. In the area of testing and research, the introduction of multiple aptitude test and the suggestion to undertake research studies to develop local informational materials, to locally standardize foreign test, and to follow up placement results were mentioned to enrich the services of the proposed program. Also, assigning student to counselors according to year level was expected to be a more effective way of bringing together the counselor and the student rather than through a highly open invitation which the students do not seem to respond to.